Flipped Classroom for Non-English Department Students: How doest it work in Geography Education Program? - Enggar Wahyu Prameswari; Elvina Arapah; Emma Rosana Febriyanti (Universitas Lambung Mangkurat, 2025)
In early 2020, the covid-19 disease spread around the world. This greatly changed the order of life of the people in the world. One of the most affected is Education, especially learning activities. Therefore, it is a challenge for teachers to make learning with an online system (Asynchronous learning) but it can still be effective to do. One of the most popular among learners is the flipped classroom. Flipped Classroom is also an alternative for teaching English to Non-English Department Students during and after the Covid-19 Pandemics. This research aims to describe how Flipped Classroom is implemented in English I Course at Geography Education Study Program in the Academic Year of 2023/2024. Narrative Inquiry method is used as the way to collect the data from the lecturer who taught the course. Findings show that certain characteristics of Flipped Classroom have been fulfilled although there are some others which are not quite exactly as required by Flipped Classroom. Since the data were obtained from the subject only, it is recommended that future research on flipped classroom should clearly describe the activities used for both in-class and out-of-class activities obtained from observations